10th Jubilee Multidisciplinary International Conference of Neuroscience and Biological Psychiatry "Stress and Behavior". (29th August 2007) - Kalueff, Allan V.
Abstract : St. Petersburg (Russia) hosted the 10th Jubilee Multidisciplinary Conference Stress and Behavior during May 1620, 2007. The conference featured many foremost researchers speaking on recent developments on topics such as the role of neural plasticity, memory, learning, genetics, neuromediators, transporters, and steroids in stress research, spanning disciplines from fields ranging from neurogenetics to clinical psychiatry. The conference was attended by 700 delegates from over 40 nations.